2015
DOI: 10.1111/ina.12181
|View full text |Cite
|
Sign up to set email alerts
|

The IVAIRE project - a randomized controlled study of the impact of ventilation on indoor air quality and the respiratory symptoms of asthmatic children in single family homes

Abstract: NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 41 publications
0
20
0
2
Order By: Relevance
“…One of these studies estimated that VRs increased by 0.18 L/s with added MV; however, indoor CO 2 concentrations decreased by only 16%, compared to a 9% decrease in control homes. In the second of these studies, the VR increased by 0.17 h −1 in intervention homes compared to a 0.03 h −1 increase in control homes.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…One of these studies estimated that VRs increased by 0.18 L/s with added MV; however, indoor CO 2 concentrations decreased by only 16%, compared to a 9% decrease in control homes. In the second of these studies, the VR increased by 0.17 h −1 in intervention homes compared to a 0.03 h −1 increase in control homes.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, 11 of 20 studies reported a SS improvement in one or more health outcomes with increased VRs or with lower CO 2 concentrations that indicate higher VRs. Most of these studies included assessments of multiple additional health outcomes that were not statistically significantly associated with VRs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisher ist in der Literatur nur eine Interventionsstudie im Kindesalter publiziert, die auch Messungen der Formaldehyd-Konzentration in der Innenraumluft umfasste [3]. In ihr wurden 83 asthmatische Kinder im Alter von 3-12 Jahren, die in schlecht belüfteten Wohnräumen (Lüftungsra-ten unter 0,3 h -1 , im Mittel 0,18 h -1 ) lebten, über 2 Jahre verfolgt.…”
Section: Interventionsstudienunclassified
“…In gesundheitlicher Hinsicht wurden bei der primären Zielvariablen "Anzahl der Tage mit Symptomen" keine Unterschiede zwischen den Gruppen beobachtet. Aber in der Interventionsgruppe wurde eine verminderte Häufigkeit folgender sekundä-rer Zielvariablen gefunden: mindestens eine Wheezing-Episode im Jahr zu ha-m 3 …”
Section: Interventionsstudienunclassified